GABA‐, histamine‐, and FMRFamide‐immunoreactivity in the visual, vestibular and central nervous systems of Hermissenda crassicornis. Issue 16 (11th August 2017) - Webber, Marissa P.; Thomson, James W. S.; Buckland‐Nicks, Johnny; Croll, Roger P.; Wyeth, Russell C.
Abstract: Hermissenda crassicornis is a model for studying the molecular and cellular basis for classical conditioning, based on its ability to associate light with vestibular stimulation. We used confocal microscopy to map histamine (HA), FMRF‐amide, and γ‐aminobutyric acid (GABA) immunoreactivity in the central nervous system (CNS), eyes, optic ganglia and statocysts of the nudibranchs. For HA immunoreactivity, we documented both consistently and variably labeled CNS structures across individuals. We also noted minor differences in GABA immunoreactivity in the CNS compared to previous work on Hermissenda . Contrary to expectations, we found no evidence for GABA inside the visual or vestibular systems. Instead, we found only FMRFamide‐ and HA immunoreactivity (FMRFamide: 4 optic ganglion cells, 4–5 hair cells; HA: 3 optic ganglion cells, 8 hair cells). Overall, our results can act as basis for comparisons of nervous systems across nudibranchs, and suggest further exploration of intraspecific plasticity versus evolutionary changes in gastropod nervous systems. Abstract : Immunohistochemical labeling of GABA, histamine and FMRFamide in the CNS, visual, and vestibular systems of Hermissenda crassicornis show extensive and consistent patterns of labeled somata and neuropils. Variable aspects of labeling (among preparations or in comparison to earlier reports) are indicative of intraspecific plasticity and also suggest interspecific divergence in neuroanatomy.